PENGARUH TINGKAT KEPATUHAN WAJIB PAJAK BADAN, PEMERIKSAAN PAJAK, DAN PENAGIHAN PAJAK TERHADAP PENINGKATAN PENERIMAAN PAJAK PENGHASILAN PADA KANTOR PELAYANAN PAJAK PRATAMA TAMPAN KOTA PEKANBARU - Yosi Widia Sari; Zirman -; Eka Haryani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The objective of this research was to analyze the influence of level institution of tax compliance, tax audit and tax collection toward tax revenue in the tax office of Pratama Tampan Pekanbaru. The population in this research is the company registered in the tax office of Pratama Tampan Pekanbaru in 2011 until 2013. Sample was determined by the purposive sampling method. Types of data is secondary data and the method of analysis used is multiple regression analysis. The test results of this study indicate that the level of institution of tax compliance and tax collection effect on tax revenue. Meanwhile, tax audit have no effect on tax revenue. This research suggested : 1) For further researcher should consider expanding the sample beyond the company that registered in the tax office of Pratama Tampan Pekanbaru and extend the obsevation period. 2) Many other factor that effect. For further researcher should be able to collaborate on a variety of relevant variabel in affecting tax revenue. Based on the total adjusted R-square results proved that the variable independence, level institution of tax compliance, tax audit and tax collection affect the tax revenue of 0.537 or 53.7%. While the remaining 46.3% is explained by other variables that are not performed in this research.Keywords: compliance, tax, audit, and tax service